Establishment of a uniform histological evaluation method for early stage osteophytes in the destabilization of the medial meniscus mouse model - Akihiro Jono; Yuta Yanagihara; Tomofumi Kinoshita; Masaki Takao; Yuuki Imai (Osteoarthritis and Cartilage Open, 2023)
Background: Osteophyte formation is attracting attention as an early-stage pathology of knee osteoarthritis (OA). Although osteophyte formation is understood as a defense response to joint instability, its role and impact on OA remain largely unknown. Many studies have been conducted using the surgical destabilization of the medial meniscus (DMM) mouse model, but there are few standard evaluation methods, especially in the histological evaluation of early-stage osteophytes. The purpose of this study was to establish a reproducible and uniform method for histological evaluation of characteristics of early osteophyte formation in the DMM mouse model. Methods: Male mice were operated with DMM at 12 weeks old and histologically evaluated at 4 days and 1, 2 and 4 weeks after DMM. Osteophyte Width, Osteophyte Area, and Original and Modified Maturity Scores were used to evaluate osteophytes for all sections. Results: Osteophyte Width, Osteophyte Area and Maturity Scores were all greater anteriorly than posteriorly in the knee joint. The Modified Maturity Score was more strongly correlated with position than the Original Maturity Score, and could be used to evaluate early-stage osteophyte formation. Conclusion: The Modified Maturity Score as well as Osteophyte Width and Area at the section of the anterior cruciate ligament (ACL) attachment site can provide a reproducible evaluation method to histologically assess the early-stage osteophyte formation in the DMM mouse model.